The Raslila in Krishna Bhakti Poetry : कृष्णभक्ति काव्य में रासलीला - Choudhary, Jaswant Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The Raslila holds a special significance in Krishna Bhakti poetry. The Shrimad Bhagwat Mahapurana consists of twelve cantos, eighteen thousand verses, and 335 chapters. The Bhagwat is considered the literary form of the divine, with the twelve cantos symbolizing the various parts of the divine body. Among these, the tenth canto is regarded as the heart of the divine. Within the tenth canto, chapters 29 to 33 are collectively known as the Ras Panchadhyayi, which narrate the blissful Raslila of Lord Krishna with Raseshwari. The essence of the Ras Panchadhyayi lies in the name of Shri Radha, considered supremely confidential. The five chapters are deemed the life force of the Maharas. Shukdevji also assigned twelve names to each canto, reflecting both the speaker’s persona and the essence of the events described. Similarly, the twelve cantos are collectively referred to as Dwadasharanya (the twelve forests), with each forest narrating blissful divine pastimes. The tenth canto is termed the Paramatmaranya (the supreme forest of the divine), and within it, the Ras Panchadhyayi is regarded as the Swarooparanya (the essential forest). Over time, much like the Ramayana, the enactment of Raslila allowed the masses to directly experience devotion and faith by participating in it. Additionally, its portrayal evolved through various art forms. Abstract in Hindi Language: कृष्णभक्ति काव्य में रासलीला का विशेष महत्व है। श्रीमद्भागवत महापुराण में बारह स्कंध, अठारह हजार श्लोक, और 335 अध्याय हैं। भागवत भगवान की वाङ्मयी मूर्ति कहलाती है तथा बारह स्कंधों की अंग-प्रत्यंग की कल्पना की गई है। भागवत के बारह स्कंध भगवान के बारह अंग माने जाते हैं। इनमें भी दशम स्कंध को भगवान का हृदय कहा गया है। इसमें दशम स्कंध पूर्वार्ध के अध्याय 29 से 33 तक पाँच अध्याय रास पंचाध्यायी कहलाते हैं, जिसमें भगवान की रास रासेश्वरी की रसपूर्ण लीला का वर्णन है। रास पंचाध्यायी का भी सार श्रीराधा जी का नाम है, जिसे परम गोपनीय माना गया है। पाँचों अध्याय महारास के प्राण रूप माने जाते हैं। शुकदेव जी के भी प्रत्येक स्कंध के अनुसार बारह नाम हैं। इन नामों से वक्ता का स्वरूप तथा सभी प्रसंगों का स्वरूप दीखता है। इसी प्रकार बारह स्कंधों को स्वरूपानुसार द्वादशारण्य कहा गया है। सभी अरण्यों में उनके नामानुसार आनंदमयी लीलाओं का वर्णन किया गया है। दशम स्कंध को परमात्मारण्य कहा गया है। इसमें भी रास पंचाध्यायी को स्वरूपारण्य कहा गया है। आगे चलकर रामायण की तरह रासलीला के अनुकरण द्वारा जनसाधारण भक्ति और श्रद्धा का प्रत्यक्ष अनुभव करने के लिए उसमें भाग लेने लगा। साथ ही, इसके स्वरूप का विभिन्न कला माध्यमों द्वारा विकास होता गया। Keywords: श्रीमद्भागवत पुराण, रासलीला, पुराण, भक्ति काव्य, कला।